Construction site erosion and sediment controls : planning, design and performance - Pitt, Robert; Clark, Shirley E.; Lake, Donald W. (DEStech Publications, Inc., 2020)
This is an expanded and updated edition of a textbook initially published in 2006 and used extensively as a practical reference by engineers in the field and as a textbook by professors of civil engineering. The book covers important recent technical and regulatory advances on how to assess and control runoff from sites being excavated for building and development. In technology, it explains new methods of containment and monitoring, with many original site-based problems and engineering strategies to address them. In particular, it explains the requirements for developing erosion-control plans that meet local, state, and EPA stormwater requirements. Emerging systems for calculating and predicting runoff and its effects are also presented, including the evolving connections between rainfall data and localized erosion. A fuller discussion of U.S. and international standards is provided. In addition, the revised volume contains more problems and projects for civil engineering instructors and students.
Keywords: Building sites -- Planning.; Soil conservation.; Sediment control.; elektronické knihy; electronic books